Kajian Dam Break Waduk Wonogiri Dengan Hec-Ras 4.0 - Rohani, Ichwan Dwi, Gurawan Djati Wibowo, ST., M.Eng, Ir. Achmad Karim Fatchan.,M.T (2017)
Dam is water building which serves to stem the flow of the river order to obtain water reservoir river. To making dam must is designed with standard security high that the dam secure against overtopping ( to flooding plan ), a piping and burden the devastating earthquake. Dam in wonogiri was huge we need to meet the security standards applied of them are analysis and break when a when there was rupture or collapse so of the surrounding community and part downstream can save self that not hit by hack flood . Evaluation of these floods using rainfall data were 9 stations include stations Slogohimo, station Jatisrono, station Girimarto PP, station Sidoharjo, station Ngancar, station Baturetno PP, station Giriwoyo, station Kedung Uling and stations Wuryantoro divided into 5 DAS include DAS Kedoang, Temon DAS, Bengawan solo upstream DAS, Posong DAS and Kedung Uling DAS. Flooding due Dam Break searches in reservoirs and Gajah Mungkur use application methods HEC - RAS 4.0 According to the comparison of the results of the hydrograph QPMF, Q1000 years, Q100 years and Q50 years, QPMF larger. Radiation flood hydrograph downstream to the naked eye can translasion, damped (reduced) by more downstream flood peak is getting smaller. The maximum flood peak attenuation (PMF flood hydrograph) is point most downstream (in AWLR Jurug), by 23%. Attenuation of flood peak maximum possible (flood hydrograph Q1000 yrs) is point most downstream (in AWLR Jurug), of 15%, the attenuation of flood peak maximum possible (flood hydrograph Q100 yrs) is dititik most downstream (in AWLR Jurug), of 13%, the maximum flood peak attenuation (Q50 flood hydrograph yrs) is point most downstream (in AWLR Jurug), of 12%. Results of search analytics Dam break flood due to the application of HEC - RAS 4.0 shows the results of the data flood hydrograph when through in the dam body QPMF, Q1000 years, Q100 years and Q50 years, the greater QPMF the nearest future, the highest elevation and high speed.